Legal Legality Ir. Soekarno in the City of Ende and the History of the Birth of Pancasila - Prisko Yanuarius Djawaria Pare; Konstantinus Dua Dhiu (PT FORMOSA CENDEKIA GLOBAL, 2022)
In Indonesian history, there are many heroes known. National history proves that every time and age gave birth to Indonesian heroes. One of them was Ir Soekarno, who the Indonesian people called the father of the proclaimer. The history of Ir Soekarno's struggle to liberate the Indonesian state from Dutch colonialism was also inseparable from periods of exile in various places. The implementation method used is observation or direct observation at the Bung Karno historical site. The method of carrying out the research was carried out by direct observation, interviews with historical sources and actors, documentation at the Bung Karno exile house and Bung Karno's Pancasila contemplation garden. This research is actually dedicated to remembering the history of Bung Karno's struggle in formulating and sparking the basis and philosophy of life for the Indonesian nation, namely formulating the noble values of Pancasila under the breadfruit tree, and reflecting deeply on the foundations of the unitary state of the Republic of Indonesia which is called Pancasila.